Developing a Motion Comic for HIV/STD Prevention for Young People Ages 15–24, Part 2: Evaluation of a Pilot Intervention. Issue 3 (4th March 2018) - Willis, Leigh A.; Kachur, Rachel; Castellanos, Ted J.; Nichols, Kristen; Mendoza, Maria C. B.; Gaul, Zaneta J.; Spikes, Pilgrim; Gamayo, Ashley C.; Durham, Marcus D.; LaPlace, Lisa; Straw, Julie; Staatz, Colleen; et al.
ABSTRACT: In the United States, young people (ages 15–24 years) are disproportionately affected by human immunodeficiency virus (HIV) and other sexually transmitted diseases (STDs), due at least in part to inadequate or incorrect HIV/STD-related knowledge, attitudes, beliefs, and behavioral intentions (KABI). Comic book narratives are a proven method of HIV/STD prevention communication to strengthen KABI for HIV/STD prevention. Motion comics, a new type of comic media, are an engaging and low-cost means of narrative storytelling. The objective of this study was to quantitatively evaluate the effectiveness of a pilot six-episode HIV/STD-focused motion comic series to improve HIV/STD-related KABI among young people. We assessed change in HIV/STD knowledge, HIV stigma, condom attitudes, HIV/STD testing attitudes, and behavioral intentions among 138 participants in 15 focus groups immediately before and after viewing the motion comic series. We used paired t -tests and indicators of overall improvement to assess differences between surveys. We found a significant decrease in HIV stigma ( p < .001) and increases in both HIV knowledge ( p = .002) and behavioral intentions to engage in safe sex ( p < .001). In summary, this motion comic intervention improved HIV/STD-related KABI of young adult viewers by reducing HIV stigma and increasing behavioral intentions to engage in safer sex. Our results demonstrate the promise of this novel intervention and support its use to deliver health messages to young people.